2007
DOI: 10.1002/mrd.20837
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a donor mitochondrial DNA transmission bottleneck in nuclear transfer derived cow lineages

Abstract: In embryos derived by nuclear-transfer (NT), fusion of donor cells with recipient oocytes resulted in varying patterns of mitochondrial DNA (mtDNA) transmission in NT animals. Distribution of donor cell mtDNA (D-mtDNA) found in offspring of NT-derived founders may also vary from donor cell and host embryo heteroplasmy to host embryo homoplasmy. Here we examined the transmission of mtDNA from NT cows to G(1) offspring. Eleven NT founder cows were produced by fusion of enucleated oocytes (Holstein/Japanese Black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…In higher mammals, the segregation of donor mtDNA through the germ-line bottleneck was assessed previously only indirectly, using tissues of a few SCNT offspring [47].…”
Section: Selection Against Donor Mitochondriamentioning
confidence: 99%
“…In higher mammals, the segregation of donor mtDNA through the germ-line bottleneck was assessed previously only indirectly, using tissues of a few SCNT offspring [47].…”
Section: Selection Against Donor Mitochondriamentioning
confidence: 99%
“…Although most bovine SCNT offspring show mtDNA genotypes that differ from those of the targeted (founder) animals ( Fig. 1) [9,10], nuclear transfer is regarded as the most effective technique to exchange mtDNA in a single generation [4,11]. The main reason for mitochondrial respiration defects in mitochondrial diseases is accumulation of pathogenic mutant mtDNAs; therefore, nuclear transfer has been considered the most effective treatment strategy to preferentially eliminate mutant mtDNA molecules or to dilute the molecules to below a threshold proportion for the expression of disease phenotypes.…”
Section: Transmission Of Mitochondrial Dna In Cloned Cattle and Pigsmentioning
confidence: 99%
“…CA3 and CA4 exhibited a mixture of genotypes with D-mtDNA [79] more sequence variants in a cell, a genetic bottleneck in the female germ line will generally favor the transmission of a single mitochondrial population (homoplasmy) [13,27,28]. However, in SCNT animals both stable and unstable transmission of D-mtDNA was found in porcine and bovine G n s [10,17]. In our study, D-mtDNA was present at ranges of 0.1-1.0 % of total mtDNA in SCNT pigs derived from Chinese pig (Meishan breed) fibroblasts microinjected into European pig oocytes (maternal Landrace breed) [29].…”
Section: Transmission Of Mitochondrial Dna In Cloned Cattle and Pigsmentioning
confidence: 99%
“…It has been demonstrated that donor mitochondrial DNA (mtDNA) is transmitted to clone offspring with varying efficiencies (Takeda et al, 2008). Four cows (F1) with mtDNA heteroplasmy showed normal growth, productivity and lactation characteristics and productivity.…”
Section: Dna Mutations and Mtdna Heteroplasmymentioning
confidence: 99%